HUBUNGAN BURNOUT PERAWAT DENGAN TINDAKAN PENCEGAHAN DAN PENGENDALIAN INFEKSI DI RUANG RAWAT INAP RS JUANDA KUNINGAN - Yeni Widyani (2023)
Health is very important for a persons life in order to be able to carry out daily activities comfortably. Hospitals as health service providers for the community play an important role in maximizing the level of health of a community, but conditions in the field show that not a few people who seek treatment at hospitals have the opportunity to get new diseases that have not been suffered before or HAIs (Healthcare Associated Infections). The purpose of this study was to determine the relationship between nurse burnout to infection prevention and control measures inpatient room of Juanda Kuningan Hospital. This research was conducted in May 2023 using a descriptive analytic research method with a cross sectional approach. Sampling was a total sampling of 75 respondents. The results of the chi square test obtained a p value <0,05 (0,002), which means that there is a relationship between nurse burnout and infection prevention and control measures. The recommendation from this study is that hospital managers needs to improve the quality of nurses by supervising and preventing burnout in nurses to take proper infection prevention and control (PPI) measures.